Self-Regulated Learning in Student with Online Learning System - Lubis, Susi Handayani Br. (PT. BATARI EDU CALYA, 2024)
This research aims to explore and understand more deeply the application of self-regulated learning among students who attend lectures with an online system. The research method used is a qualitative approach with a phenomenological design. The research subjects were selected using purposive sampling techniques, and data were collected through observation and in-depth interviews. This research focuses on one student subject who takes online lectures. The findings of the study show that subjects apply self-regulation in learning through three main phases, namely: (1) Forethought, (2) Performance, and (3) Reflection. The Forethought phase includes planning and self-confidence, the Performance phase involves self-regulation and observation, and the Reflection phase includes self-assessment and evaluation. The results of this study are expected to provide valuable insights into self-regulation strategies in the context of online lectures and recommendations for students to improve the effectiveness of their learning.